Balloon Aortic Valvuloplasty – Remaining Indications in the Modern TAVR Era. Issue 3 (3rd May 2020) - Ooms, Joris F.; van Wiechen, Maarten P.; Ziviello, Francesca; Kroon, Herbert; Ren, Ben; Daemen, Joost; de Jaegere, Peter; Van Mieghem, Nicolas M.
ABSTRACT: Objectives: : A retrospective observational cohort study to report on contemporary indications of balloon aortic valvuloplasty (BAV). Background: : As indications for transcatheter aortic valve replacement (TAVR) are increasing, BAV is reinforced as a bridging therapy. Methods: : A total of 47 consecutive patients who underwent BAV in parallel to an existing TAVR program was retrospectively assessed for BAV indications and clinical events during 1 year of follow-up. Results: : The following indications were distinguished: bridge to destination aortic valve replacement therapy (BTD), bridge to urgent non-cardiac therapy (BTN) or palliation. BAV was performed in 20 (43%) patients as BTD, in 18 (38%) as BTN and in 9 (19%) as palliative treatment. Patients in the BTN cohort were younger (age 74.1 ± 8.3% vs. 80.7 ± 8.3% years in BTD, p = 0.02) with lower STS-scores (2.2% [IQR 1.3–4.6] vs. 13.0% [IQR 7.6–22.2] p < 0.001). Overall baseline mean transaortic gradient was 43.2 mmHg and reduced by a mean of 16.0 ± 10.1 mmHg after BAV ( p < 0.001). Procedural mortality was 8.5% (n = 4). All-cause mortality at 30 days and 1 year was 20% and 45% in BTD, 6% and 39% in BTN and 44% and 67% in the palliative group. Aortic valve replacement (AVR) was performed in 55% of the BTD and 50% of the BTN group at 1 year. Reasons for not undergoing definite AVR were clinical deterioration in BTD and terminal comorbidity in BTN. Compared to a contemporary TAVR cohort, procedural and 1 year mortality was significantly increased in the BAV cohort. Conclusion: : BAV remains a valuable option in well-defined patient phenotypes to determine AVR feasibility, bridge to urgent non-cardiac therapy, and at times, palliation. These phenotypes represent vulnerable patients with overall poor clinical outcome.